Investigating Non-steroidal Anti-Inflammatory Drugs as Potential Cancer Adjuncts: A Novel Approach to Cancer Therapy - Sadaf Alam; Leena Anjum; Muhammad Haneef (RADS Journal of Biological Research & Applied Science)
Purpose: This review aims to evaluate the chemo preventive and therapeutic potential of non-steroidal anti-inflammatory drugs (NSAIDs) in cancer management, emphasizing their mechanisms of action and clinical relevance.